Surgical Outcomes in Cases of Marcus-Gunn Jaw-Winking Phenomenon - Sthapit, RP; Saiju, R (Kathmandu University Medical Journal, 2015)
Background Markus-Gunn Jaw-winking Phenomenon (MGJW) is a congenital ptosis associated with synkinetic movement of upper lid on masticating movements of jaw. It results from aberrant connection between motor division of trigeminal nerve and oculomotor nerve.Objective To investigate the clinical characteristics of MGJW phenomenon and evaluate its surgical outcomes of unilateral levator excision and frontalis suspension.Method It is a retrospective analysis of nine cases of MGJW phenomenon seen from 2007 to 2013 AD. The clinical features were recorded and analysed. Unilateral levator excision and frontalis suspension for the correction of synkinesis and ptosis was done for all the patients. The result of surgery was analysed.Result MGJW phenomenon was seen more in males. All the cases had unilateral ptosis with jaw winking phenomenon. Ipsilateral hypotropia and refractive errors were seen in 44%. One week post operative margin reflex distance was good in 67% of cases. Persistent jaw-winking was seen in 3 cases, two underwent repeat surgery to abolish the synkinesis. At one year follow up, 33% had good margin reflex distance of more than 4mm and 22% had fairly good margin reflex distance of 3mm.Conclusion Patients with Marcus Gunn jaw winking synkinesis can present at a wide age range. There may be an associated vertical muscle imbalance, which should be managed before ptosis surgery to avoid ptosis under correction. Unilateral frontalis flap suspension combined levator excision can correct ptosis very well for patients with Marcus-Gunn syndrome.Kathmandu University Medical Journal Vol.13(1) 2015; 34-37